Climate shocks, institutional investors, and the information content of stock prices - Blanco, Ivan; Martin-Flores, Jose M.; Remesal, Alvaro (Journal of Corporate Finance, 2024)
We analyze how the materialization of physical climate risk in the institutional investors’ portfolios spurs a propagation effect on the information content of stock prices. Institutional investors with a relatively high portfolio exposure to natural disasters divest from disaster-hit stocks, decrease the trading intensity in non-hit stocks, and their trading decisions predict low medium-term returns. At the firm-level, institutional investors propagate the effects of disasters to non-hit stocks through reduced incorporation of firm-specific information, especially when the stocks represent a low portfolio weight. Combined, these results suggest that natural disasters trigger a rational reallocation of information-processing resources by institutional investors.